PENGEMBANGAN MEDIA PEMBELAJARAN SMART RABBIT BERBASIS ESD UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS SISWA SDN SUKARUKUN 01 - Rahmadaniati, Rahma; Setiawan, Bramianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop Smart Rabbit learning media based on Education for Sustainable Development (ESD) to improve first-grade students’ mathematical concept understanding at SDN Sukarukun 01 on addition material. The research employed the Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Media validation by media experts, language experts, and material experts using the CVR and CVI obtained the maximum score of 1.00, indicating excellent content validity. Practicality tests through teacher and student response questionnaires showed scores of 94% from teachers and 97.1% from students, indicating that the media is highly practical and engaging for learning activities. Effectiveness testing using a pretest-posttest design and N-Gain analysis score 0.79 demonstrated a significant improvement in students’ mathematical concept understanding, with results categorized as effective. Therefore, the Smart Rabbit learning media based on ESD is feasible and effective for enhancing mathematical concept understanding among elementary school students.